RANCANG BANGUN PROPELLER TURBIN ANGIN SUMBU VERTICAL BERBAHAN DASAR KOMPOSIT FIBERGLASS (GFRP) - TA Nizardi; syurkarni ali; Zakir Husin; Mahmuddin Marbun (universitas teuku umar, 2021)
The wind energy as an alternative in the use of renewable energy has the potential to increase income for the capital, where the potential for wind in the area of Meulaboh, west Aceh, which is 11 km/h, on average can be used for electrical energy needs specially for low wind turbine power, This is research is designing and manufacturing wind turbine propellers. Wind type Lenz cupped type, the number of propellers as much as 3 (three) pieces. The design method is carried out by using Sketch Up software, the final result is in the form of a 3-D image and in the manufacturing process method is making the wind turbine propeller with the method hand lay up for the materials using are fiberglass as a matrix and resin as a reinforcement or known as composite materials. And to obtain the results, a test was carried out in the form of a propeller ability test in driving a generator. With the generator output was 100 W. The test was carried out at the location of Teuku Umar University in an integrated building, precisely on the rooftop with a height of build ± 50m. On the sea level. The results obtained after testing the wind speed amounted to 18.4 mph. average during testing 3 (three) days, and the average results of the propeller turbine rotation of 39.8 rpm. Key words: wind energy, energy alternative, composite materials, hand lay up, wind speed, propeller turbine rotation